Method for preparing precoated sand by using cast steel waste sand

By regenerating cast steel waste sand and reasonably adding components, efficient and low-cost coated sand is prepared, which solves the problems of high production costs and insufficient recycling in the existing technology, and realizes effective recycling of resources and the performance of castings.

CN119387492APending Publication Date: 2025-02-07LIUZHOU LIUJING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411517706.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The production cost of existing cast steel coated sand is high and the recycling of cast steel waste sand is insufficient, resulting in waste of resources and increased production costs.

Method used

Recycled sand is prepared by crushing, firing, granulating and heating the cast steel waste sand, and adding aluminum sol, phenolic resin, urotine and calcium stearate to the stirring environment to prepare film sand .

Benefits of technology

It reduces the production cost of coated sand, improves the quality of recycled sand, reduces the pore occurrence and crack defects of the casting, and improves the strength and surface finish of the casting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005107170260000091
    Figure BDA0005107170260000091
  • Figure BDA0005107170260000101
    Figure BDA0005107170260000101
Patent Text Reader

Abstract

The invention discloses a method for preparing precoated sand by using cast steel waste sand, and belongs to the technical field of casting, and the method comprises the following steps: preparing regenerated sand by using the cast steel waste sand, heating the regenerated sand, sequentially adding alumina sol, phenolic resin, urotropine and calcium stearate into the heated regenerated sand in a stirring environment, and mixing to obtain the precoated sand. The method has the beneficial effects that the steel casting waste sand is used for preparing the reclaimed sand, so that the steel casting waste sand is recycled, the production cost is saved, and meanwhile green production is achieved; and the prepared reclaimed sand has the excellent properties of lower expansion coefficient, lower acid consumption value and the like, and can be matched with other components of the precoated sand to generate a better effect during production of the precoated sand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of casting, and in particular to a method for preparing coated sand by utilizing waste steel casting sand. Background Art

[0002] Cast steel coated sand is a new type of coated sand product with excellent high temperature performance and comprehensive casting performance. Cast steel coated sand has the characteristics of high strength, fast curing speed, high SiO2 content, strong high temperature resistance, low gas emission, good fluidity, etc. It is a molding material widely used in valve housings, buffer joints, steel shafts, engineering excavators, container corner parts and other cast steel parts. The existing cast steel coated sand has the problems of high production cost and low recycling of used cast steel waste sand. Summary of the invention

[0003] In order to overcome the problems of high production cost of cast steel coated sand in the prior art and low recycling of used cast steel waste sand, the present invention provides a method for preparing coated sand using cast steel waste sand, comprising:

[0004] Step 1, crushing the waste steel casting sand and separating the metal blocks;

[0005] Step 2, burning the crushed cast steel waste sand;

[0006] Step 3, granulating the fired waste steel casting sand to obtain regenerated sand;

[0007] Step 4: heat the regenerated sand, and add aluminum sol, phenolic resin, hexamethylenetetramine and calcium stearate into the heated regenerated sand in a stirring environment to obtain coated sand.

[0008] Preferably, the coated sand comprises the following components by weight: 1000 parts of regenerated sand, 1.2-2.5 parts of aluminum sol, 25-35 parts of phenolic resin, 11-14 parts of urotropine, and 1.8-2.4 parts of calcium stearate.

[0009] Preferably, the silicon dioxide content in the waste steel casting sand is greater than 99%.

[0010] Preferably, the steel casting waste sand is Hainan sand waste sand.

[0011] Preferably, in step 2, the waste cast steel sand is subjected to a first crushing and a second crushing in sequence, and the diameter of the waste cast steel sand after the first crushing is 1-10 cm. Subsequently, the waste cast steel sand is placed in a drum crushing device for a second crushing and metal blocks are separated, and the diameter of the waste cast steel sand after the second crushing is less than 6 mm.

[0012] Preferably, the firing temperature is 620-680° C. and the firing time is 5-7 hours.

[0013] Preferably, after the firing is completed, the temperature of the waste steel casting sand is reduced to below 90° C. before granulation is performed.

[0014] Preferably, the AFS coefficient of the regenerated sand is 60-80, the content below 200 mesh is <0.20%, the mud content is <0.20%, the acid consumption value is <7.0ml, the angular coefficient is <1.25, the loss on ignition is <0.10%, and the expansion coefficient is <0.75%.

[0015] Preferably, the temperature of the regenerated sand is 150-160°C.

[0016] Preferably, the phenolic resin is added 15-25 seconds after the aluminum sol is added; after the hexamethylenetetramine is added, the calcium stearate is added after the water in the regenerated sand mixture is removed.

[0017] Beneficial effects:

[0018] The beneficial effects produced by the technical solution of the present invention are as follows:

[0019] (1) The regenerated sand provided by the present invention has a better particle shape, a lower acid consumption value, and a smaller mud content. Therefore, when preparing coated sand, it has a higher strength than when using the same amount of resin in the original Hainan sand, which makes it possible to reduce the addition of resin when preparing coated sand. As the resin content decreases, the gas emission of the coated sand core is relatively low, which can reduce the occurrence of pores in castings.

[0020] (2) After regeneration and roasting, the waste sand of cast steel has expanded (expansion begins at 575°C). When it is used for casting again, it has a smaller expansion coefficient, which can effectively reduce the crack defects of cast steel and reduce the deformation of castings.

[0021] (3) When aluminum sol comes into contact with hot regenerated sand, the acidity of aluminum sol can reduce the acid consumption value of the regenerated sand, thereby improving the strength of the coated sand; furthermore, through mixing, the aluminum sol can be attached to the surface of the sand particles, which can effectively improve the refractoriness of the sand, thereby obtaining a casting with a smooth surface. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the present invention will be clearly and completely described in conjunction with the embodiments below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Therefore, the following detailed description of the embodiments of the present invention provided is not intended to limit the scope of the claimed invention, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0023] This embodiment uses waste sand after steel casting to re-prepare regenerated sand. The prepared regenerated sand has excellent properties such as low acid consumption value, low mud content, and low expansion coefficient. The regenerated sand is used as raw sand to prepare coated sand for steel casting. The specific implementation is as follows:

[0024] A method for preparing coated sand using waste steel casting sand comprises:

[0025] Step 1, crushing the waste steel casting sand and separating the metal blocks;

[0026] Step 2, burning the crushed cast steel waste sand;

[0027] Step 3, granulating the fired waste steel casting sand to obtain regenerated sand;

[0028] Step 4: heat the regenerated sand, and add aluminum sol, phenolic resin, hexamethylenetetramine and calcium stearate into the heated regenerated sand in a stirring environment to obtain coated sand.

[0029] Specifically, the coated sand contains the following components in parts by weight: 1000 parts of regenerated sand, 1.2-2.5 parts of aluminum sol, 25-35 parts of phenolic resin, 11-14 parts of urotropine, and 1.8-2.4 parts of calcium stearate.

[0030] Specifically, the content of silicon dioxide in the waste sand is greater than 99%.

[0031] Specifically, the steel casting waste sand is Hainan sand waste sand.

[0032] Specifically, in step 2, the waste steel sand is crushed for the first time and for the second time in sequence, and the diameter of the waste steel sand after the first crushing is 1-10 cm. Subsequently, the waste steel sand is placed in a drum crushing device for the second crushing and metal blocks are separated, and the diameter of the waste steel sand after the second crushing is less than 6 mm.

[0033] Specifically, the firing temperature is 620-680° C. and the firing time is 5-7 hours.

[0034] Specifically, after the firing is completed, the temperature of the waste steel casting sand is reduced to below 90° C. before granulation.

[0035] Specifically, the AFS coefficient of the regenerated sand is 60-80, the content below 200 mesh is less than 0.20%, the mud content is less than 0.20%, the acid consumption value is less than 7.0 ml, the angular coefficient is less than 1.25, the loss on ignition is less than 0.10%, and the expansion coefficient is less than 0.75%.

[0036] Specifically, the temperature of the regenerated sand is 150-160°C.

[0037] Specifically, phenolic resin is added 15-25 seconds after aluminum sol is added; after hexamethylenetetramine is added, calcium stearate is added after water in the regenerated sand mixture is removed.

[0038] The functions of each component in the coated sand are:

[0039] As the original sand, the regenerated sand has high SiO2 content and reasonable particle size distribution, which can effectively prevent sand sticking to steel castings. It also has a small angular coefficient and moderate particle size, which can make the sand particles closer to a round shape. With the same amount of resin added, the resin film is thicker, which is beneficial to improving the strength of the sand core.

[0040] Phenolic resin as a binder and aluminum sol as an auxiliary agent both play a role in enhancing the strength of coated sand, improving the fluidity of coated sand, improving refractoriness and improving the surface smoothness of coated sand. However, excessive addition of either phenolic resin or aluminum sol will increase the brittleness of the sand mold, reduce its bearing capacity, and thus affect the casting effect.

[0041] Hexamethylenetetramine, as a curing agent, plays a role in accelerating curing, enhancing strength, improving wear resistance and heat resistance in coated sand, but its excessive use will lead to problems such as increased brittleness of the coated sand, reduced fluidity and defects on the surface of the coated sand.

[0042] The main functions of calcium stearate in cast steel coated sand include improving fluidity, strength and heat resistance. Calcium stearate is evenly distributed in the coated sand and can soften and melt with phenolic resin at the core making temperature to form an interpenetrating network, increasing the softness and thermal toughness of the phenolic resin. Excessive calcium stearate will reduce the strength and heat resistance of the coated sand. In addition, too much calcium stearate may cause the lubrication effect between the sand particles to be too strong, which will affect the fluidity and filling performance of the sand mold and increase the generation of pores and defects; it will also affect the curing effect of the resin, resulting in insufficient hardness and stability of the sand mold. Excessive calcium stearate may cause the lubrication effect between the sand particles to be too strong, which will affect the fluidity and filling performance of the sand mold and increase the generation of pores and defects.

[0043] The present invention will be further described below through specific examples and comparative examples:

[0044] Example 1

[0045] In this embodiment, the coated sand includes the following components by weight: 1000 parts of regenerated sand, 1.2 parts of aluminum sol, 25 parts of phenolic resin, 11 parts of urotropine, and 1.8 parts of calcium stearate.

[0046] The preparation process of coated sand in this embodiment includes:

[0047] Step 1, selecting waste steel casting sand for crushing, the waste steel casting sand is Hainan sand waste sand with a silicon dioxide content of 99.5%, and sequentially performing a first crushing and a second crushing on the selected waste steel casting sand to separate metal blocks;

[0048] Step 2: Put the crushed waste steel sand into a roasting furnace and burn it at 620°C for 5 hours;

[0049] Step 3, placing the fired waste steel sand into a spray flow tank to cool down to 85°C, and then placing the waste steel sand into two groups of six-layer granulators for granulation and sieving out the residual fine powder to obtain regenerated sand;

[0050] Step 4: Heat the regenerated sand to 150° C. in a mixer, add aluminum sol and mix for 15 seconds, then add phenolic resin and mix evenly, add hexamethylenetetramine and remove the moisture in the mixer, then add calcium stearate and mix evenly to obtain coated sand.

[0051] Example 2

[0052] In this embodiment, the coated sand includes the following components by weight: 1000 parts of regenerated sand, 2 parts of aluminum sol, 30 parts of phenolic resin, 13 parts of urotropine, and 2 parts of calcium stearate.

[0053] The preparation process of coated sand in this embodiment includes:

[0054] Step 1, selecting waste steel casting sand for crushing, the waste steel casting sand is Hainan sand waste sand with a silicon dioxide content of 99.5%, and sequentially performing a first crushing and a second crushing on the selected waste steel casting sand to separate metal blocks;

[0055] Step 2: Put the crushed waste steel sand into a roasting furnace and burn it at 650°C for 6 hours;

[0056] Step 3, placing the fired waste steel sand into a spray flow tank to cool down to 80°C, and then placing the waste steel sand into two groups of six-layer granulators for granulation and sieving out the residual fine powder to obtain regenerated sand;

[0057] Step 4: Heat the regenerated sand to 155° C. in a mixer, add aluminum sol and mix for 20 seconds, then add phenolic resin and mix evenly, add hexamethylenetetramine and remove the moisture in the mixer, then add calcium stearate and mix evenly to obtain coated sand.

[0058] Example 3

[0059] In this embodiment, the coated sand includes the following components by weight: 1000 parts of regenerated sand, 2.5 parts of aluminum sol, 35 parts of phenolic resin, 14 parts of urotropine, and 2.4 parts of calcium stearate.

[0060] The preparation process of coated sand in this embodiment includes:

[0061] Step 1, selecting waste steel casting sand for crushing, the waste steel casting sand is Hainan sand waste sand with a silicon dioxide content of 99.5%, and sequentially performing a first crushing and a second crushing on the selected waste steel casting sand to separate metal blocks;

[0062] Step 2: Put the crushed waste steel sand into a roasting furnace and burn it at 680°C for 7 hours;

[0063] Step 3, placing the fired waste steel sand into a spray flow tank to cool down to 70°C, and then placing the waste steel sand into two groups of six-layer granulators for granulation and sieving out the residual fine powder to obtain regenerated sand;

[0064] Step 4: Heat the regenerated sand to 160° C. in a mixer, add aluminum sol and mix for 25 seconds, then add phenolic resin and mix evenly, add hexamethylenetetramine and remove the moisture in the mixer, then add calcium stearate and mix evenly to obtain coated sand.

[0065] Comparative Example 1

[0066] In this comparative example, the coated sand includes the following components in parts by weight: 1000 parts of regenerated sand, 1 part of aluminum sol, 30 parts of phenolic resin, 10 parts of urotropine, and 2 parts of calcium stearate.

[0067] The preparation process of the coated sand in this comparative example is the same as that in Example 2.

[0068] Comparative Example 2

[0069] In this comparative example, the coated sand includes the following components, by weight: 1000 parts of regenerated sand, 3 parts of aluminum sol, 30 parts of phenolic resin, 16 parts of urotropine, and 2 parts of calcium stearate.

[0070] The preparation process of the coated sand in this comparative example is the same as that in Example 2.

[0071] Comparative Example 3

[0072] In this comparative example, the coated sand includes the following components, by weight: 1000 parts of regenerated sand, 2 parts of aluminum sol, 23 parts of phenolic resin, 13 parts of urotropine, and 2 parts of calcium stearate.

[0073] The preparation process of the coated sand in this comparative example is the same as that in Example 2.

[0074] Comparative Example 4

[0075] In this comparative example, the coated sand includes the following components in parts by weight: 1000 parts of regenerated sand, 2 parts of aluminum sol, 31 parts of phenolic resin, 13 parts of urotropine, and 2 parts of calcium stearate.

[0076] The preparation process of the coated sand in this comparative example is the same as that in Example 2.

[0077] Comparative Example 5

[0078] In this comparative example, the coated sand includes the following components, measured by weight: 1000 parts of regenerated sand, 2 parts of aluminum sol, 30 parts of phenolic resin, 13 parts of urotropine, and 1.6 parts of calcium stearate.

[0079] The preparation process of the coated sand in this comparative example is the same as that in Example 2.

[0080] Comparative Example 6

[0081] In this comparative example, the coated sand includes the following components, measured by weight: 1000 parts of regenerated sand, 2 parts of aluminum sol, 30 parts of phenolic resin, 13 parts of urotropine, and 2.7 parts of calcium stearate.

[0082] The preparation process of the coated sand in this comparative example is the same as that in Example 2.

[0083] Comparative Example 7

[0084] The components and quantities of the coated sand in this comparative example are the same as those in Example 2.

[0085] The silicon dioxide content of the waste steel casting sand in this comparative example is 98%.

[0086] The preparation process of the coated sand in this comparative example is the same as that in Example 2.

[0087] Comparative Example 8

[0088] The components and quantities of the coated sand in this comparative example are the same as those in Example 2.

[0089] The firing temperature of the waste steel casting sand in this comparative example is 600°C.

[0090] The rest of the preparation process of the coated sand in this comparative example is the same as that in Example 2.

[0091] Comparative Example 9

[0092] The components and quantities of the coated sand in this comparative example are the same as those in Example 2.

[0093] The firing time of the waste steel casting sand in this comparative example is 4.5h.

[0094] The rest of the preparation process of the coated sand in this comparative example is the same as that in Example 2.

[0095] Comparative Example 10

[0096] The components and quantities of the coated sand in this comparative example are the same as those in Example 2.

[0097] In this comparative example, the water in the mixer was not removed after the addition of hexamethylenetetramine.

[0098] The rest of the preparation process of the coated sand in this comparative example is the same as that in Example 2.

[0099] Comparative Example 11

[0100] The components and quantities of the coated sand in this comparative example are the same as those in Example 2.

[0101] In this comparative example, normal Hainan sand was used instead of regenerated sand as the original sand in the coated sand.

[0102] The rest of the preparation process of the coated sand in this comparative example is the same as that in Example 2.

[0103] The regenerated sand in this embodiment and the comparative example was tested, and the test results are shown in Table 1. The coated sand prepared in this embodiment and the comparative example was then tested for high temperature resistance, gas evolution, fluidity and other properties according to the national standard JB / T8583-2008 "Coated Sand for Casting". The detailed test results are shown in Table 2.

[0104] Table 1 Regenerated sand performance table

[0105]

[0106]

[0107] Table 2 Coated sand performance test results

[0108] Room temperature tensile strength (MPa) High temperature resistance time(s) Gas generation (mL / g) Liquidity(s) Example 1 4.5 240 14.8 17.7 Example 2 4.8 250 15.1 17.5 Example 3 5.2 260 16.1 16.9 Comparative Example 1 4.4 190 15.2 17.5 Comparative Example 2 4.8 215 16.9 17.7 Comparative Example 3 3.6 183 14.2 17.6 Comparative Example 4 5.5 260 17.5 17.9 Comparative Example 5 3.9 175 15.2 22.7 Comparative Example 6 4.2 186 16.1 16.8 Comparative Example 7 3.7 182 16.4 20.1 Comparative Example 8 3.9 195 16.3 19.8 Comparative Example 9 3.6 196 16.5 19.1 Comparative Example 10 3.7 151 17.5 19.0 Comparative Example 11 3.2 176 18.1 22.5

[0109] Combining the test performance results of the regenerated sand and the coated sand in Table 1 and Table 2, it can be seen from Examples 1 to 3 that the coated sand prepared within the ratio and preparation conditions given in the present invention has excellent high temperature resistance, low gas evolution and good fluidity; from the comparison between Example 2 and Comparative Examples 1 to 6, it can be found that when the components in the coated sand are less than or more than the range given in the present invention, the strength, high temperature resistance, gas evolution and fluidity of the coated sand will be negatively affected; from the comparison between Example 2 and Comparative Examples 7, 8, and 9, we can see that when the silica content in the waste sand is too low or the firing temperature / firing time is not enough, the prepared regenerated sand will be reduced. The quality of raw sand, thereby deteriorating the performance of the coated sand finally produced; in the preparation process of coated sand, the moisture in the mixer is removed before adding calcium stearate in order to reduce the moisture and gas generation in the later coated sand, so as to avoid affecting the strength and gas generation of the coated sand. Combining Example 2 with Comparative Example 10, we can see that the strength and fluidity of the coated sand from which the moisture has not been removed are significantly deteriorated; and combining Example 11 with Comparative Example 11, we can find that the regenerated sand prepared by the method provided by the present invention has a better shape (angular coefficient), lower ignition loss and expansion coefficient than ordinary Hainan sand, and the prepared coated sand also has better quality.

[0110] The present invention prepares regenerated sand by using waste sand from steel casting with a silicon dioxide content higher than 99%, so that the waste sand after steel casting is recycled, which saves production costs and realizes green production. The prepared regenerated sand has excellent properties such as low expansion coefficient and acid consumption value, and can be combined with other components of coated sand to produce better effects when producing coated sand. For example, after the regenerated sand is fired, it has a smaller expansion coefficient, which can effectively reduce the crack defects of cast steel and reduce the deformation of castings; the regenerated sand has a better angular coefficient, a lower acid consumption value and a smaller mud content, so it has a higher strength when preparing coated sand. At the same time, the addition of resin can be reduced at the same strength, so that the gas emission of the coated sand core is relatively low, which can reduce the occurrence of pores in castings.

[0111] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing coated sand using waste steel casting sand, characterized in that: include: Step 1, crushing the waste steel casting sand and separating the metal blocks; Step 2, burning the crushed waste steel casting sand; Step 3, granulating the fired waste steel casting sand to obtain regenerated sand; Step 4: heating the regenerated sand, and sequentially adding aluminum sol, phenolic resin, hexamethylenetetramine and calcium stearate into the heated regenerated sand in a stirring environment to obtain coated sand.

2. The method for preparing coated sand using waste cast steel sand according to claim 1, characterized in that: The coated sand comprises the following components in parts by weight: 1000 parts of the regenerated sand, 1.2-2.5 parts of the aluminum sol, 25-35 parts of the phenolic resin, 11-14 parts of the urotropine, and 1.8-2.4 parts of the calcium stearate.

3. The method for preparing coated sand using waste cast steel sand according to claim 1, characterized in that: The silicon dioxide content in the waste steel casting sand is greater than 99%.

4. The method for preparing coated sand using waste steel casting sand according to claim 1, characterized in that: In the step 2, the waste steel sand is crushed for the first time and for the second time in sequence. The diameter of the waste steel sand after the first crushing is 1-10 cm. Subsequently, the waste steel sand is placed in a drum crushing device for the second crushing and metal blocks are separated. The diameter of the waste steel sand after the second crushing is less than 6 mm.

5. The method for preparing coated sand by using waste cast steel sand according to claim 1, characterized in that: The firing temperature is 620-680°C and the firing time is 5-7h.

6. The method for preparing coated sand by using waste steel casting sand according to claim 1, characterized in that: After the firing is completed, the temperature of the waste steel casting sand is reduced to below 90° C. before granulation.

7. The method for preparing coated sand by using waste steel casting sand according to claim 1, characterized in that: The AFS coefficient of the regenerated sand is 60-80, the content below 200 mesh is less than 0.20%, the mud content is less than 0.20%, the acid consumption value is less than 7.0ml, the angular coefficient is less than 1.25, the ignition loss is less than 0.10%, and the expansion coefficient is less than 0.75%.

8. The use of waste steel casting sand to prepare regenerated sand according to claim 1, characterized in that: The temperature of the regenerated sand is 150-160°C.

9. The use of waste steel casting sand to prepare regenerated sand according to claim 1, characterized in that: After the hexamethylenetetramine is added, the calcium stearate is added after the water in the regenerated sand mixture is removed.